2015
DOI: 10.1128/aem.02503-14
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-Mediated Iron Acquisition Influences Motility and Is Required for Full Virulence of the Xylem-Dwelling Bacterial Phytopathogen Pantoea stewartii subsp. stewartii

Abstract: Iron is a key micronutrient for microbial growth but is often present in low concentrations or in biologically unavailable forms. Many microorganisms overcome this challenge by producing siderophores, which are ferric-iron chelating compounds that enable the solubilization and acquisition of iron in a bioactive form. Pantoea stewartii subsp. stewartii, the causal agent of Stewart's wilt of sweet corn, produces a siderophore under iron-limiting conditions. The proteins involved in the biosynthesis and export of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 58 publications
2
23
0
1
Order By: Relevance
“…P. aeruginosa ), require iron for biofilm assembly: low iron triggers increased surfactant production and motility, which in turn reduces biofilm structure (30, 31). Similar connections between iron availability and motility have been made in other microbes (3235). Streptomyces exploration is phenotypically similar to sliding motility – a form of passive motility driven by growth and facilitated by the release of a surfactant.…”
Section: Discussionsupporting
confidence: 68%
“…P. aeruginosa ), require iron for biofilm assembly: low iron triggers increased surfactant production and motility, which in turn reduces biofilm structure (30, 31). Similar connections between iron availability and motility have been made in other microbes (3235). Streptomyces exploration is phenotypically similar to sliding motility – a form of passive motility driven by growth and facilitated by the release of a surfactant.…”
Section: Discussionsupporting
confidence: 68%
“…Usually, hydroxamates are more commonly found in neutral to acid environments while catecholates are more commonly found in neutral to alkaline environments (Saha et al, 2013). Several bacterial genera were described to produce siderophores, such as Azotobacter (Baars et al, 2016;McRose et al, 2017;Romero-Perdomo et al, 2017), Azospirillum (Banik et al, 2016), Bacillus (Kesaulya et al, 2018;Pourbabaee et al, 2018), Dickeya (Sandy and Butler, 2011), Klebsiella (Bailey et al, 2018;Zhang et al, 2017), Nocardia (Hoshino et al, 2011), Pantoea (Burbank et al, 2015;Soutar and Stavrinides, 2018), Paenibacillus (Liu et al, 2017), Pseudomonas (Baune et al, 2017;Deori et al, 2018;Pourbabaee et al, 2018), Serratia (Coulthurst, 2014) and Streptomyces (Gáll et al, 2016;Goudjal et al, 2016;Schütze et al, 2014).…”
Section: Siderophoresmentioning
confidence: 99%
“…Pantoea stewartii subsp. stewartii produces a siderophore under iron-limiting conditions, which biosynthesis and export of proteins are encoded by the iucABCD-iutA operon; this operon is homologous to the aerobactin biosynthetic gene cluster found in a number of enteric pathogens (Burbank et al, 2015). It was also described that the strain Pantoea eucalypti M91 is capable of producing pyoverdine-like and pyochelin-like siderophores under alkaline growth conditions (Campestre et al, 2016).…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…campestris (Dow et al, 2003;Tao et al, 2010), Pantoea stewartii subsp. stewartii (Leigh & Coplin, 1992;Burbank et al, 2015) and Clavibacter michiganensis (Marques et al, 2002;Chalupowicz et al, 2012), biofilm formation has been reported as an important factor associated with virulence, since it allows a higher resistance to plant defenses and competition with other species (Ramey et al, 2004). Garcia et al (2013) observed that R. solanacearum isolates were actively virulent against pepper (Capsicum annuum), tomato (Solanum lycopersicum), eggplant (S. melongena) and tobacco (Nicotiana tabacum), confirming the results obtained in our study for the same isolates, since most of they were moderate or strong biofilm producers.…”
Section: Discussionmentioning
confidence: 99%